2011
DOI: 10.1016/j.biomaterials.2010.11.066
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Aβ(1-40) amyloid fibrils under tensile loading

Abstract: Amyloid fibrils and plaques are detected in the brain tissue of patients affected by Alzheimer's disease, but have also been found as part of normal physiological processes such as bacterial adhesion. Due to their highly organized structures, amyloid proteins have also been used for the development of novel nanomaterials, for a variety of applications including biomaterials for tissue engineering, nanolectronics, or optical devices. Past research on amyloid fibrils resulted in advances in identifying their mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
59
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 67 publications
8
59
0
Order By: Relevance
“…S11, E and F, for a comparison of the model and experimentally measured fibril dimensions). Such effects have been described previously (26,47). It has been shown that a gradual increase in the number of monomers in a fibril FIGURE 5 Ashby plot summarizing this study.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…S11, E and F, for a comparison of the model and experimentally measured fibril dimensions). Such effects have been described previously (26,47). It has been shown that a gradual increase in the number of monomers in a fibril FIGURE 5 Ashby plot summarizing this study.…”
Section: Discussionmentioning
confidence: 81%
“…Of interest here is the use of AFM to determine the mechanical properties of amyloid fibrils such as persistence length (1,2,4,23), Young's (elastic) modulus (1,5,24), and strength (25). Constant-velocity steered molecular dynamics (SMD) simulations have also been used effectively to calculate the rupture force in tensile deformation simulations, allowing for estimation of the ultimate strength and Young's (elastic) modulus of amyloid fibrils (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, estimations of Young's moduli of amyloid fibrils by simulations point at numbers in the same order of magnitude as experimental values, yet, systematically higher. [18][19][20][21] Recently, we have reported that peak force quantitative nanomechanical (PF-QNM) AFM shows great potential to be applied as a high-resolution technique to identify structural features and associated nanomechanical properties of amyloid fibrils. 22 Here we further demonstrate that the technique is insensitive to the structural details of the amyloid fibril cross-section, that is to say that the intrinsic stiffness expressed by Young's modulus can be correctly de-coupled from the overall rigidity, to which both Young's modulus and cross-section contribute.…”
Section: Introductionmentioning
confidence: 99%
“…The biological implication of this model is that extremely short fibrils are flexible and ductile whereas longer fibrils are stiff and brittle (38) [if we assume, as experiment suggests (39), that fibril fracture occurs through the breakage of longitudinal hydrogen bonds]. Higher rupture forces would be required to fragment low aspect ratio fibrils, because they can deform through shear, whereas longer, high aspect ratio fibrils would become increasingly fractureprone due to the L −2 scaling of critical buckling force for an Euler-Bernoulli beam (36).…”
mentioning
confidence: 99%